The problems of proteinuria measurement in urine with presence of Bence Jones protein - Maisnar, Vladimír; Tichý, M; Stulik, J; Vavrova, J; Friedecky, B; Palička, Vladimír; Spirková, J; Žaloudková, Lenka; Hernychová, Lenka; Spáčilová, J; Büchler, Tomáš; Hájek, Roman (Clinical biochemistry, 2011)
OBJECTIVES: Protein concentration measurement in the urine can be problematic in the presence of Bence Jones protein. We have carried out an external quality control assessment with the participation of 79 clinical biochemistry laboratories from the Czech Republic and Slovakia. DESIGN AND METHODS: The laboratories received a reference urine sample obtained from a patient with multiple myeloma and lambda free light chain proteinuria and were asked to type the paraprotein using immunofixation and to measure total urinary protein using their established method, most commonly turbidimetry, pyrogallol red assay, and biuret assay. RESULTS: There was a very wide inter-laboratory variability in the protein concentration readouts with up to three-fold difference in some cases. High-resolution two-dimensional electrophoresis and linear mass spectrometry showed that a high proportion of the urinary paraprotein was composed of lambda light chain fragments with molecular weight of 12kDa. CONCLUSIONS: Our results highlight the challenges of reliable and reproducible measurement of urinary protein concentration in the presence of Bence Jones protein.
Keywords: Proteinuria; Electrophoresis, Gel, Two-Dimensional; Reproducibility of Results; 2D gelová elektroforéza; lidé; reprodukovatelnost výsledků; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Bence-Jonesova bílkovina; Bence Jones Protein; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; proteinurie; Humans